ON A SUPPOSED INCOHERENCE BETWEEN KANT’S VIEW ON HOMOSEXUALITY AND HIS VIEW ON AUTONOMY - Nahra, Cinara (Princípios: Revista de Filosofia (UFRN), 2015)
There are some very respectable Kant commentators who argue that Kant was not justified in using his own theory to reach the conclusions that he reached in relation to the immorality of homosexuality and some sex-related matters such as marriage and prostitution. Guyer argues that the principle that every natural organ and capacity has one and only one proper use (the teleological principle of living beings) has no fundamental normative role within Kant’s moral philosophy and although Kant does use this principle, in some aspects of his treatment of human sexuality and in some of his arguments against suicide, he has no justification for doing so. From Guyer’s viewpoint, the adoption of this principle seems to be incompatible with his fundamental principle of the unconditional value of human freedom. Denis believes that appeals to nature’s purpose for particular drives constitute a limited part of Kant’s arguments for duties to ourselves, concluding that there seems to be no support for the view that homosexual sex is wrong and that it cannot, like heterosexual sex, be made permissible by being put into a context of a mutually respectful relationship. But are these the correct interpretations of Kant’s views? Is it true that a) the teleological principle of living beings has no normative role in Kant’s philosophy, b) that appeals to nature and the ends of nature have only a limited role in Kant’s moral philosophy and c) that the right application of the Categorical imperative would never lead to the conclusions that Kant draws, that homosexuality is immoral? Here in this article it will be discussed Kant’s view on homosexuality and how Kant justifies it. The analysis carried out will show (contrarily to Guyer and Denis) that the role of the teleological principle and the Formule of the Universal Law of Nature (FLUN) - act as if the maxim of your action were to become by your will a universal law of nature - in Kant´s discussion of homosexuality is fundamental to the conclusions that he arrives on the immorality of homosexuality, suggesting that both , the teleological principle and the FLUN, have a role that is far from secondary in Kant’s moral system. The next step is to analyze how (and if) Kant’s views on homosexuality and Kant’s strong reliance on the teleological principle to ground this condemnation are consistent with his views on freedom and autonomy. The surprising conclusion is that, contrarily to contemporary interpretations of Kant’s moral philosophy, Kant’s views on homosexuality are not inconsistent with his idea of autonomy, but rather, a full comprehension of his concept of autonomy (positive freedom), requires teleological presuppositions, especially those related to the purpose of the sexual instinct in preserving the species and the purpose of the instinct of self-love in the conservation of our lives.